Social norms and family planning decisions in South Sudan - Sumit Kane; Maryse Kok; Matilda Rial; Anthony Matere; Marjolein Dieleman; Jacqueline EW Broerse (BMC, 2016)
Abstract Background With a maternal mortality ratio of 789 per 100,000 live births, and a contraceptive prevalence rate of 4.7%, South Sudan has one of the worst reproductive health situations in the world. Understanding the social norms around sexuality and reproduction, across different ethnic groups, is key to developing and implementing locally appropriate public health responses. Methods A qualitative study was conducted in the state of Western Bahr el Ghazal (WBeG) in South Sudan to explore the social norms shaping decisions about family planning among the Fertit community. Data were collected through five focus group discussions and 44 semi-structured interviews conducted with purposefully selected community members and health personnel. Results Among the Fertit community, the social norm which expects people to have as many children as possible remains well established. It is, however, under competitive pressure from the existing norm which makes spacing of pregnancies socially desirable. Young Fertit women are increasingly, either covertly or overtly, making family planning decisions themselves; with resistance from some menfolk, but also support from others. The social norm of having as many children as possible is also under competitive pressure from the emerging norm that equates taking good care of one's children with providing them with a good education. The return of peace and stability in South Sudan, and people's aspirations for freedom and a better life, is creating opportunities for men and women to challenge and subvert existing social norms, including but not limited to those affecting reproductive health, for the better. Conclusions The sexual and reproductive health programmes in WBeG should work with and leverage existing and emerging social norms on spacing in their health promotion activities. Campaigns should focus on promoting a family ideal in which children become the object of parental investment, rather than labour to till the land - instead of focusing directly or solely on reducing family size. The conditions are right in WBeG and in South Sudan for public health programmes to intervene to trigger social change on matters related to sexual and reproductive health; this window of opportunity should be leveraged to achieve sustainable change.